2006
DOI: 10.1590/s1516-35982006000400020
|View full text |Cite
|
Sign up to set email alerts
|

Exigências de aminoácidos sulfurados digestíveis para suínos machos castrados e fêmeas de 15 a 30 kg

Abstract: -A trial was conducted with fifty pigs (Landrace x Large White), barrows and gilts, from 15 to 30 kg, in the initial growing phase to determine the digestible sulfur amino acids requirements. The animals were allotted to a completely randomized experimental block design, with five treatments (0.502, 0.530, 0.558, 0.586, and 0.614% of digestible methionine plus cystine), five replicates and two animals (one male and one female) per experimental unit. It was observed quadract effect of treatments on daily weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
3
1
1
Order By: Relevance
“…Evaluating dietary SID Met + Cys levels for barrows and gilts (15-30 kg), Moura et al (2006) observed a better ADG at 5.82 g/kg of SID Met + Cys, which is lower than the obtained in this study (6.61 g/kg). The NRC (2012) proposed 6.8 g/kg SID Met + Cys as the requirement for barrows and gilts, that is close to the optimum level obtained for the ADG in the current study (6.61 g/kg).…”
Section: Discussioncontrasting
confidence: 90%
“…Evaluating dietary SID Met + Cys levels for barrows and gilts (15-30 kg), Moura et al (2006) observed a better ADG at 5.82 g/kg of SID Met + Cys, which is lower than the obtained in this study (6.61 g/kg). The NRC (2012) proposed 6.8 g/kg SID Met + Cys as the requirement for barrows and gilts, that is close to the optimum level obtained for the ADG in the current study (6.61 g/kg).…”
Section: Discussioncontrasting
confidence: 90%
“…Vaz et al (2005) and Moura et al (2006) observed a lower fat deposition in the carcasses of growing pigs, while Pena et al (2008) obtained the lowest cholesterol levels in the loin and backfat of finishing pigs fed a diet with a Met + Cys/lysine ratio of 0.66.…”
Section: Resultsmentioning
confidence: 95%
“…According to Le Bellego and Noblet (2002) and Moura et al (2006), the possible amino acid imbalance caused by a deficiency or Table 4 -Plasma levels of glucose, urea, creatinine, triglycerides, and total protein in female pigs from 75 to 100 kg fed diets containing different levels of standardized ileal digestible (SID) methionine + cystine (Met+Cys) and B 6 vitamin supplementation excess of SID Met+Cys in the diet negatively influences the voluntary food intake of the animals. Despite the varying SID Met+Cys levels (0.370-0.670%) evaluated in this study, the ADFI of the animals was not affected.…”
Section: Discussionmentioning
confidence: 99%